Захист мереж доступу на базі технології Wi-Fi - Сливар, У. М. (ХНУРЕ, 2025)
This work enhances Wi-Fi security by adding two-factor authentication with Google Authenticator. A one-time password (OTP) changes every minute, preventing brute-force and WPS attacks. Testing confirms improved protection against unauthorized access.
Keywords: захист мереж доступу; Wi-Fi